CONCENTRATION OF CYTOKINES (IL-4, IL-12, IFNγ) IN THE BLOOD PLASMA AND ITS ASSOCIATION WITH LYMPHOCYTE APOPTOSIS IN PATIENTS SUFFERING FROM CHRONIC LYMPHOCYTIC LEUKEMIA - Dejanović, Hristina; Jovanović, Danijela (Srpski medicinski časopis Lekarske komore, 2023)
Introduction: Chronic lymphocytic leukemia (CLL) is a malignant disease of hematopoietic tissue and is the most common leukemia in adults. For years, the dominant view was that in the pathogenesis of chronic lymphocytic leukemia, the basic mechanism of the origin and progression of the disease is disruption in apoptosis and prolonged survival of malignant lymphocytes.Aim: The aim of our study is to determine the association between the percentage of apoptotic lymphocytes in the peripheral blood of patients suffering from chronic lymphocytic leukemia and the concentration of antiapoptotic cytokines (IL-4, IL-12, IFNγ) in the patients’ blood plasma. Materials and methods: The study included 29 patients suffering from chronic lymphocytic leukemia (21 men and 8 women) who had not been on a chemotherapy regimen in the preceding 6 months. Clinical parameters (clinical stage of disease, presence of lymphadenopathy, splenomegaly), biochemical parameters (LDH), and the type and percentage of bone marrow infiltration were determined in all patients. The percentage of apoptotic lymphocytes and the concentration of cytokines (IL-4, IL-12, IFNγ) in the patients' plasma were determined from the patients' peripheral blood.Results: In the studied group of patients, plasma concentration values of IL-4 = 121.42 pg/ml (62.44 – 180.40), IL-12 = 7.62 pg/ml (4.36 – 10.87), IFNγ = 31.45 pg/ml (18.35 – 44.56) were detected. In the cell population, less than 1% of apoptotic cells were detected, ranging from 0.03% to a maximum of 0.84%. The results show no correlation between the concentration of cytokines and the percentage of apoptotic lymphocytes in the patients’ peripheral blood, however, they show that Il-12 concentration positively correlates with the stage of the disease, as well as with the percentage of bone marrow infiltration by malignant lymphocytes (p < 0.001 or p = 0.028).Conclusion: Plasma concentrations of IL-4, IL-12, IFNγ are not correlated with the percentage of apoptotic lymphocytes in the peripheral blood of patients with chronic lymphocytic leukemia. Interleukin-12 nevertheless shows a positive correlation in advanced disease.
Keywords: chronic lymphocytic leukemia; apoptosis; cytokines